Comparative analysis of the sin-hyperbolic and Kachanov–Rabotnov creep-damage models. (March 2019) - Haque, Mohammad Shafinul; Stewart, Calvin Maurice
Abstract: In this study, the Sin-Hyperbolic (Sinh) and the classic Kachanov-Rabotnov (KR) creep-damage models are fit to creep data for 304 stainless steel at 600 and 700 °C. The ability of the models to predict minimum creep strain rate, creep deformation, damage evolution, and rupture are compared. It is shown that both models can predict the creep deformation accurately; however, the minimum creep strain rate, damage evolution, and rupture predictions of the KR model is deficient. Using the KR model, critical damage is often less than unity; a violation of continuum damage mechanics (CDM). The KR minimum creep strain rate and rupture predictions do not exhibit the sigmoidal bend on a log-log scale that is observed in experimental data. In the Sinh model, critical damage is always unity and the sigmoidal bend in the minimum creep strain rate and stress-rupture curves is present. Overall the Sinh model is more accurate. Highlights: The performance of the Sinh and Kachanov-Rabotnov creep-damage models are compared. The Kachanov–Rabotnov model exhibits poor minimum creep strain rate, damage evolution, and rupture predictions. Overall, the Sinh model is more accurate.